Recognition of SA Heart - Doubell, AF (SA Heart Journal, 2017)
SA Heart is listed by the Department of Education (DoE) as an Approved Journal since January 2009. This development is important, not only for the stature of the Journal, but also for practical reasons such as the subsidy from the DoE involved for authors affiliated to academic institutions.